STUDY OF CHOLESTEROL CONTENT IN THE ORAL FLUID OF PATIENTS WITH PERI-IMPLANTITIS AGAINST THE BACKGROUND OF THE TREATMENT AND PREVENTION COMPLEX - Adubetska, A.Y.; Shnaider, S.A.; Skyba, V.Ya.; Skulska, S.V.; Godovanets, O.I.; Novikova, Zh.O.; Khodorchuk, K.V. (World of Medicine and Biology, 2025)
The study was devoted to researching of the effect of the treatment and prevention complex on the cholesterol content in the oral fluid of patients with peri-implantitis. The study involved 40 patients with peri-implantitis aged 25 to 55 years. Indicators of oral lipid metabolism – cholesterol – were determined in the patients’ oral fluid. In patients receiving the treatment and prevention complex, the level of cholesterol in the oral fluid decreased by 25 % after one month of therapy compared to the baseline. After three months, it decreased by another 2.1 times, approaching the level observed in healthy individuals. In patients in the comparison group, who received only the standard treatment protocol, the level of cholesterol in the oral fluid remained persistently elevated throughout the study period, which emphasizes the need for additional interventions to achieve a significant normalization of lipid metabolism in peri-implantitis.